China’s Security Apprehension and Strategic Interests in Afghanistan - Samiullah; Mehboob Ali Khan; Ibtasam Ali; Tanzila Aslam (ASIAN Journal of International Peace & Security (AJIPS), 2022)
The United States’ withdrawal from Afghanistan has increased China’s security concerns. Beijing is attempting to protect Xingjian province from possible East Turkistan Islamic Movement cross-border incursion (ETIM). This research paper examines China’s security concerns and strategic interests in Afghanistan, and how these have evolved over time. China’s apprehension with respect to Afghanistan is shaped by its concerns regarding the spread of terrorism, extremism, and separatism in its Xinjiang region, which borders Afghanistan. China’s strategic interests in Afghanistan are driven by its desire to secure its energy supplies, protect its investments in the region, and expand its economic influence in South Asia. The research analyses China’s involvement in the Afghanistan peace process, its relations with the Taliban, and its growing military and economic presence in the region. The paper argues that China’s engagement in Afghanistan is driven by a desire to safeguard its security interests, expand its global influence, and counterbalance the United States in the region.